Practical Broad-Band Tuning of Dye Lasers by Solvent Shifting. Issue 6 (1986) - Grenci, Susan M.; Bird, George R.; Keelan, Brian W.; Zewail, Ahmed H.
Abstract : We have operated a dye laser over a broad wavelength range (593.8–667.0 nm) by shifting the dye emission profile with incremental changes of solvent composition. This was accomplished with the laser operating continuously, and only minor adjustment of the laser optics was required. Solvent tuning was facilitated by the critical dependence of the optimum laser wavelength on concentration of the second solvent. Using the known solvent-sensitive laser dye 9-diethylaminobenzo[a]phenoxaz-5-one (DBP), 87% of the tuning range from pure xylenes to pure methanol was covered by cumulative addition of 24 vol. % methanol to the starting xylenes solution. The optimum dye concentration was found to be independent of solvent composition, so that maximum laser power could be maintained by mixing equimolar dye solutions in the two solvents. These results establish the practicality of solvent-tuning as a method of conducting laser experiments over a broad wavelength range.